Language and word processing areas of the human brain - Abdulrahman, Shilan O.; Farhadi, Prof. Dr. Sajida A. (Mitanni Journal of Humanitarian Sciences, 2023)
Summary The human brain is like a computer. It is better to say that the computer is like the human brain. The human brain is the first and most capable of storing. Another characteristic of the human brain is that it can mark everything around it, and put a code for everything in the form of words and keep them in special places Where words are stored in the brain, not only words, but also how to speak, express, write and picture things. They are stored with words and can be restored and used when needed.